2012
DOI: 10.1128/mbio.00312-12
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LpxC Protects Mice from Resistant Acinetobacter baumannii by Modulating Inflammation and Enhancing Phagocytosis

Abstract: New treatments are needed for extensively drug-resistant (XDR) Gram-negative bacilli (GNB), such as Acinetobacter baumannii. Toll-like receptor 4 (TLR4) was previously reported to enhance bacterial clearance of GNB, including A. baumannii. However, here we have shown that 100% of wild-type mice versus 0% of TLR4-deficient mice died of septic shock due to A. baumannii infection, despite having similar tissue bacterial burdens. The strain lipopolysaccharide (LPS) content and TLR4 activation by extracted LPS did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 61 publications
6
144
3
Order By: Relevance
“…Studies have attributed septic shock associated with A. baumannii infections to bacterial LPS and outer membrane shedding in secreted outer membrane vesicles by the bacterium (14,44,45). However, data presented here suggest that this may not be the case, but rather, elevated PTX3 production induced by select A. baumannii strains appears to correspond with increased susceptibility of mice to infection.…”
Section: Figcontrasting
confidence: 53%
See 3 more Smart Citations
“…Studies have attributed septic shock associated with A. baumannii infections to bacterial LPS and outer membrane shedding in secreted outer membrane vesicles by the bacterium (14,44,45). However, data presented here suggest that this may not be the case, but rather, elevated PTX3 production induced by select A. baumannii strains appears to correspond with increased susceptibility of mice to infection.…”
Section: Figcontrasting
confidence: 53%
“…A similar association between elevated PTX3 production and disease severity has been observed following both Gram-positive and Gram-negative sepsis in human patients (29)(30)(31)(32)(33)35); however, at this time we cannot discern if the effects observed here are due in part to other entities, e.g., inflammatory molecules. Interestingly, although studies examining A. baumannii bloodstream infections involving hypercoagulability and DIC have attributed these symptoms to bacterial LPS and outer membrane shedding (14,44,45), data presented here indicate that disease severity was dependent on interaction of live bacteria with the immune system, as evidenced by the complete lack of mortality in mice challenged with UV-killed or HK bacteria administered at high inocula (Fig. 2).…”
Section: Figmentioning
confidence: 82%
See 2 more Smart Citations
“…Lin et al found that an LpxC inhibitor blocked the ability of bacteria to activate the sepsis cascade, enhanced opsonophagocytic killing of A. baumannii, and protected mice from lethal infection. 38 Moreover, the potential contributions of PMB and AgNPs both involve Lipid A of LPS, a convergence which supports their synergistic effects.…”
Section: Discussionmentioning
confidence: 99%